Las tic y el ingreso en las Pymes exportadoras del estado de Yucatán - Manuel J. Caro Encalada; Carlos E. Leyva Morales; Miguel Maga\~na Maga\~na; Samuel Alvarado Yah (Atlantic Review of Economics, 2015)
– Using an econometric model is analyzed the impact on income (as an indicator of competitiveness) of the degree of use of information and communication technologies by exporting Pymes operating in the State of Yucatán. Nine of the developed models explained properly and enough that the use of ICT with a proper training of systems users, a correct use value and an proper level of computer security influence significantly in the increase of the percentage of income that perceive exporting Pymes in the State of Yucatán; However, is showed up that who makes decisions in Pymes is unknown to the computerization process allows the organizational objectives and maximize the value of it to let work with greater efficiency, better ability to response, alignment to strategy and reduction in costs.
Keywords: C12; C32; F17; M15; 330; ICT; competitiveness; small and medium-sized enterprises; export; hypothesis testing and P values